2005
DOI: 10.1103/physrevb.71.054416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tunneling magnetoresistance and magnetization in dipolar-coupled nanoparticle arrays

Abstract: The tunneling magnetoresistance (TMR) of a hexagonal array of dipolar coupled anisotropic magnetic nanoparticles is studied using a resistor network model and a realistic micromagnetic configuration obtained by Monte Carlo simulations. Analysis of the field-dependent TMR and the corresponding magnetization curve shows that dipolar interactions suppress the maximum TMR effect, increase or decrease the field-sensitivity depending on the direction of applied field and introduce strong dependence of the TMR on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Finally, the magnetoresistance of the sample is defined by MRðHÞ ¼ ðRðHÞ À R S Þ=R S ¼ ðs S À sðHÞÞ=s ðHÞ [2], where R S and s S denote the saturation values of the resistivity and conductivity, respectively. figures, it is also found that the maximum TMR effects occur also at the coercive field H c .…”
Section: Theoretical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the magnetoresistance of the sample is defined by MRðHÞ ¼ ðRðHÞ À R S Þ=R S ¼ ðs S À sðHÞÞ=s ðHÞ [2], where R S and s S denote the saturation values of the resistivity and conductivity, respectively. figures, it is also found that the maximum TMR effects occur also at the coercive field H c .…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In order to calculate the net resistance of the system, we converted the two dimensional microstructure into a network resistors by connecting each pair of adjacent units by a resistor. Based on the resistor network model employed to study the TMR, it is found that the unknown potentials {F i } can be obtained by solving the set of linear equations in P ij s ij ðF i À F j Þ ¼ 0 with the boundary conditions [2], here {F i } denotes the electric potential at a node associated with the unit i and s ij is the conductivity between two particles i and j. In addition, the whole result depends closely on the magnetic configuration hm i i, which is used as input to obtain the inter-particle conductivities.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 3 more Smart Citations